2021
DOI: 10.7150/jca.62779
|View full text |Cite
|
Sign up to set email alerts
|

Bai-He-Gu-Jin-Tang formula suppresses lung cancer via AKT/GSK3β/β-catenin and induces autophagy via the AMPK/mTORC1/ULK1 signaling pathway

Abstract: Aims: Bai-He-Gu-Jin-Tang (BHGJT) is a classic Chinese formula used to treat lung cancer, while the underlying molecular mechanism remains obscure. The aim of the study was to investigate the molecular mechanism of BHGJT on lung cancer and demonstrate the potential for synergistic treatment combining BHGJT with conventional therapy. Methods: Cell viability assay, colony formation assay and EdU assay were used to determine the in vitro effects of BHGJT, and a subcutaneous xenograft model was used to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…[36] The top GO-biological process term of BHGJT's treatment in NSCLC cells was negative regulation of the apoptotic process, while BHGJT has shown an inhibitory effect on the growth of NSCLC cells by inducing cell apoptosis via the AKT/GSK3β/ β-catenin signaling pathways. [6] Interestingly, most of the key compounds in BHGJT such as kaempferol, quercetin, beta-sitosterol and stigmasterol could also trigger the apoptosis of NSCLC. The top 15 KEGG pathways were mostly enriched in the endocrine-related pathways, the inflammation and hypoxia-related pathways as well as other cancer-related pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36] The top GO-biological process term of BHGJT's treatment in NSCLC cells was negative regulation of the apoptotic process, while BHGJT has shown an inhibitory effect on the growth of NSCLC cells by inducing cell apoptosis via the AKT/GSK3β/ β-catenin signaling pathways. [6] Interestingly, most of the key compounds in BHGJT such as kaempferol, quercetin, beta-sitosterol and stigmasterol could also trigger the apoptosis of NSCLC. The top 15 KEGG pathways were mostly enriched in the endocrine-related pathways, the inflammation and hypoxia-related pathways as well as other cancer-related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] In this context, Bai He Gu Jin Tang (BHGJT) is one of the most commonly applied formulas for the treatment of lung cancer. [ 5 , 6 ] BHGJT is composed of 10 Chinese medicinal herbs: Radix Rehmanniae Praeparata (Shu Di Huang), Radix Rehmanniae (Sheng Di Huang), Radix Angelicae Sinensis (Dang Gui), Radix Paeoniae Alba (Bai Shao), Radix et Rhizoma Glycyrrhizae (Gan Cao), Radix Platycodonis (Jie Geng), Radix Scrophulariae (Xuan Shen), Bulbus Fritillariae Thunbergii (Beimu), Radix Ophiopogonis (Maidong), and Bulbus Lilii (Bai He). BHGJT is a representative formula for cough patients with Yin deficiency syndrome, characterized by cough with little sputum, hemoptysis, lean body, dry mouth, dry stool, a red tongue with a little coating and thin pulse.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a large number of experiments have confirmed the deep connection of apoptosis with the unrestricted growth and metastasis of tumor cells. One study 24 demonstrated that Baihe Gujin decoction not only induced significant cell cycle arrest through down-regulation of CDK4 and cell cycle protein D1 in the G0/G1 phase, but 350 also promoted mitochondria-dependent apoptosis through the AKT/GSK3β/ β-catenin signaling pathway. After the successful establishment of a Lewis lung cancer nude mouse model, Lv 25 observed that modified Baihe Gujin decoction combined with radiotherapy inhibited the growth of transplanted tumors and promoted the apoptosis of tumor cells in the mice, and that the mechanism may lie in the down-regulation of the expression of hypoxia-inducible factor-1α (HIF-1α), P53, and survivin mRNA and protein.…”
Section: Induction Of Apoptosis Of Tumor Cellsmentioning
confidence: 99%
“…As Table 1 shown, we briefly summarized the potential underlying molecule pathways on Baihe Gujin decoction or its active components that exerted inhibitory effects on lung cancer in vivo. 24,[55][56][57][58][59] According to TCM principles, Baihe Gujin decoction is thought to nourish Yin, hydrate the lungs, and alleviate heat. Besides, the components of this decoction are believed to possess properties that promote lung health by addressing imbalances in the body's Yin and Yang.…”
Section: Potential Mechanisms Of Baihe Gujin Decoction On Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation